“Determinant that contributes to intention of vaping among UiTM student” / Nabiela Aufa Halimy Halim and Nurul Fikrah Hamizan - Halimy Halim, Nabiela Aufa; Hamizan, Nurul Fikrah (2022)
The purpose of the study was to examine determinant that contributes to intention of vaping among uitm student. The study was carried between May until July 2022. This study employed a probability stratified sampling techniques in collecting the survey data. The result of the study revealed important findings. First, majority of the targeted respondents were agreed with that there are relationship between the attitudes, social norms and perceive behavioural control (PCB) with intention of vaping among UiTM students. Therefore, this studies uniquely positions itself to make both theoretical and empirical contributions to the multi-domain literature including management and psychology literature.